Lithium titanate composite material, preparation method thereof, battery pole piece and lithium ion battery
Patent Information
- Application Number
- CN202011312296.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2040-11-20
AI Technical Summary
[0008]本发明的主要目的在于提供一种钛酸锂复合材料及其制备方法、电池极片和锂离子电池,以解决现有的球形形貌钛酸锂的压实密度偏低导致材料能量密度的问题
[0019]应用本发明的技术方案,将上述钛锂复合物与第一导电剂依次进行混合及造粒后能够使第一导电剂物理包覆在钛源和锂源表面,并获得不同粒径的第一原料和第二原料;通过在惰性气氛下分别进行无氧烧结,能够分别获得不同粒度的碳包覆的钛酸锂复合材料(第一烧结产物和第二烧结产物)。由于上述两种烧结产物的粒度不同,因而将其应用于金属集流体上形成电池极片时,小粒径的第二烧结原料能够填充在第一烧结产物的空隙之间,这一方面能够提高其压实密度,另一方面碳包覆层的存在能提升材料的压实密度,同时提高了材料的电子电导率,也使得其还具有较高的能量密度。综上所述,采用上述方法制得的钛酸锂复合材料具有较高的压实密度,制得的电池也具有较高的能量密度和倍率性能。
Smart Images

Figure CN112397680B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium titanate battery preparation, and more specifically, to a lithium titanate composite material and its preparation method, battery electrodes, and lithium-ion batteries. Background Technology
[0002] Lithium titanate batteries offer good safety performance, long cycle life, a stable charge-discharge platform, and excellent resistance to high and low temperatures. They can also function normally in harsh environments with varying temperatures and can perform high-rate charge-discharge operations. The main drawbacks of lithium titanate batteries are their relatively low energy density and high cost. This energy density limitation is a major factor hindering the development of lithium titanate battery technology.
[0003] The energy density of materials is typically improved in the following ways:
[0004] (1) The capacity of the material itself; increasing the capacity can improve the mass energy density of the material.
[0005] (2) The compaction density of the material can increase the volumetric energy density of the material by increasing the compaction density of the material.
[0006] Currently, lithium titanate on the market has both spherical and irregular morphologies. Spherical lithium titanate has a lower compaction density, ranging from 1.9 to 2.0 g / cm³. 3 Between these parameters, the compaction density is relatively low, limiting the improvement of the material's energy density; the irregular morphology of lithium titanate results in poor processing performance, making it difficult to achieve uniform mixing during the battery slurry process.
[0007] Given the aforementioned problems, it is necessary to provide a method for preparing lithium titanate that can achieve both high compaction density and good processing performance. Summary of the Invention
[0008] The main objective of this invention is to provide a lithium titanate composite material and its preparation method, battery electrode and lithium-ion battery, so as to solve the problem of low compaction density of existing spherical lithium titanate materials, which leads to low material energy density.
[0009] To achieve the above objectives, the present invention provides a method for preparing a lithium titanate composite material, the method comprising: sequentially mixing and granulating a titanium source, a lithium source, and a first conductive agent to obtain a first raw material and a second raw material, wherein the particle size D50 of the first raw material is 9-15 μm and the particle size D50 of the second raw material is 3-7 μm; and subjecting the first raw material and the second raw material to oxygen-free sintering under an inert atmosphere to obtain a first sintered product and a second sintered product, wherein the lithium titanate composite material is a mixture of the first sintered product and the second sintered product.
[0010] Furthermore, prior to the mixing process, the preparation method of the lithium titanate composite material also includes wet grinding of the titanium source and the lithium source; preferably, the wet grinding process has a grinding solid content of 10-30%, an effective power of 0.99-1 kW, a grinding power consumption of 2-10 kWh / kg, and a particle size D after grinding. 50 The range is 0.05–0.3 μm.
[0011] Further, the titanium source is selected from titanium dioxide and / or metatitanic acid, and the lithium source is selected from lithium hydroxide and / or lithium carbonate; the first conductive agent is selected from one or more of the group consisting of carbon nanotubes, carbon fibers, graphene, and carbon black; preferably, the molar ratio of lithium to titanium in the titanium source and lithium source is 1:1.2 to 1:1.25; preferably, the weight of the first conductive agent accounts for 1 to 5 wt% of the total weight of the titanium source and lithium source.
[0012] Further, the granulation process includes: subjecting a portion of the mixture to a first spray drying device to obtain a first raw material, wherein the inlet temperature of the first spray drying device is 250–320°C, the outlet temperature is 100–120°C, and the air inlet volume is 4–6 m³ / s. 3 / h; The remaining mixture is subjected to a second spray drying in a second spray drying unit to obtain a second raw material, wherein the inlet temperature of the first spray drying unit is 250-320℃, the outlet temperature is 100-120℃, and the air inlet volume is 7-10m³ / h. 3 / h.
[0013] Furthermore, the temperature of the oxygen-free sintering process is 650–900℃, and the sintering time is 2–8 hours.
[0014] Another aspect of this application provides a lithium titanate composite material, which is prepared using the preparation method provided in this application. The composition of the lithium titanate composite material is based on Li4Ti5O. 12 / C style representation.
[0015] Another aspect of this application provides a battery electrode, including a metal current collector and a conductive coating coated on the surface of the metal current collector. The materials forming the conductive coating include a lithium titanate composite material, a second conductive agent, and a binder. The lithium titanate composite material is a lithium titanate composite material prepared using the preparation method provided in this application.
[0016] Furthermore, in the lithium titanate composite material, the weight ratio of the first sintered product to the second sintered product is 1:9 to 9:1.
[0017] Furthermore, the weight ratio of lithium titanate composite material, second conductive agent and binder is (90-96):(5-2):(5-2).
[0018] Another aspect of this application provides a lithium-ion battery, including battery electrodes, wherein the battery electrodes are the same as those provided in this application.
[0019] By applying the technical solution of this invention, the above-mentioned titanium-lithium composite material is sequentially mixed and granulated with a first conductive agent, enabling the first conductive agent to physically coat the surfaces of the titanium and lithium sources, thus obtaining first and second raw materials with different particle sizes. Through oxygen-free sintering under an inert atmosphere, carbon-coated lithium titanate composite materials (first sintered product and second sintered product) with different particle sizes can be obtained. Because the two sintered products have different particle sizes, when applied to metal current collectors to form battery electrodes, the smaller-particle-size second sintered raw material can fill the voids in the first sintered product. This increases the compaction density, and the presence of the carbon coating layer further enhances the compaction density and electronic conductivity, resulting in a higher energy density. In summary, the lithium titanate composite material prepared by the above method has a high compaction density, and the resulting battery exhibits high energy density and rate performance. Attached Figure Description
[0020] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0021] Figure 1 The SEM image of the lithium titanate composite material prepared according to Example 1 of the present invention is shown under a 2.00K magnification electron microscope.
[0022] Figure 2 The SEM image of the lithium titanate composite material prepared according to Example 1 of the present invention is shown under a 50.0K magnification electron microscope.
[0023] Figure 3 The SEM image of the surface of the lithium titanate composite material prepared according to Example 1 of the present invention after being made into an electrode is shown under a 1.00K magnification electron microscope.
[0024] Figure 4 The SEM image of the surface of the lithium titanate composite material prepared according to Example 1 of the present invention after being made into an electrode is shown under a 50.0K magnification electron microscope.
[0025] Figure 5 The cross-section of the lithium titanate composite material prepared according to Example 1 of the present invention after being made into an electrode is shown under a 1.00K electron microscope SEM image.
[0026] Figure 6 The specific capacity of an electrode made of lithium titanate composite material prepared according to Example 1 of the present invention is shown. Detailed Implementation
[0027] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.
[0028] As described in the background section, the low compaction density of existing spherical lithium titanate materials leads to problems with material energy density. To address these technical issues, this application provides a method for preparing a lithium titanate composite material. The method includes: sequentially mixing and granulating a titanium source, a lithium source, and a first conductive agent to obtain a first raw material and a second raw material. The particle size D50 of the first raw material is 9–15 μm, and the particle size D50 of the second raw material is 3–7 μm. Under an inert atmosphere, the first and second raw materials are subjected to oxygen-free sintering to obtain a first sintered product and a second sintered product. The lithium titanate composite material is a mixture of the first and second sintered products.
[0029] After sequentially mixing and granulating the aforementioned titanium-lithium composite with a first conductive agent, the first conductive agent can be physically coated onto the surfaces of the titanium and lithium sources, yielding first and second raw materials with different particle sizes. By performing oxygen-free sintering under an inert atmosphere, carbon-coated lithium titanate composite materials (first and second sintered products) with different particle sizes can be obtained. Because the two sintered products have different particle sizes, when applied to metal current collectors to form battery electrodes, the smaller-sized second sintered raw material can fill the voids in the first sintered product. This increases the compaction density. Furthermore, the presence of the carbon coating layer not only increases the compaction density but also improves the rate performance of the material. Increased compaction density leads to higher battery energy density. In summary, the lithium titanate composite material prepared using the above method has a high compaction density, and the resulting battery exhibits high energy density and rate performance.
[0030] In a preferred embodiment, prior to the mixing process, the preparation method further includes wet milling of the titanium and lithium sources. The milling process refines the particle size of the titanium and lithium sources, thereby increasing the carbon coating amount and shortening the lithium-ion infiltration reaction path, thus increasing the current density during charge and discharge. More preferably, the wet milling process has a solid content of 10–30%, an effective power of 0.99–1 kW, a milling charge of 2–10 kWh / kg, and a particle size D after milling. 50 The thickness is 0.05–0.3 μm. Controlling the grinding solids content, effective power, and grinding charge during the wet grinding process within the above range is beneficial to further increase the coating amount of the first conductive agent, thereby further improving the rate performance and energy density of the battery.
[0031] In the above preparation method, the titanium source, lithium source and the first conductive agent can be selected from commonly used types in the art. For example, the titanium source includes, but is not limited to, titanium dioxide and / or metatitanic acid, and the lithium source includes, but is not limited to, lithium hydroxide and / or lithium carbonate. The first conductive agent is selected from one or more of the group consisting of carbon nanotubes, carbon fibers, graphene and carbon black.
[0032] Because a certain amount of lithium is lost during the sintering process, it is usually necessary to add slightly more lithium than the predetermined amount to compensate for this loss. Preferably, the weight ratio of titanium source to lithium source is 1:1.2 to 1:1.25.
[0033] The conductive agent acts as a collector of microcurrents between active materials and between active materials and current collectors, thereby reducing electrode contact resistance, increasing electron migration rate in lithium batteries, and reducing battery polarization. Simultaneously, it can improve the processing performance of battery electrodes and promote electrolyte wetting of the electrodes, thus extending the lifespan of the lithium battery. Preferably, the weight of the first conductive agent accounts for 1-5 wt% of the total weight of the titanium and lithium sources. Limiting the amount of the first conductive agent within this range is beneficial for further reducing the conductivity resistance of the battery electrodes and improving their lifespan.
[0034] The above granulation process can be carried out using commonly used processes in the art. Preferably, the above granulation process is a spray drying process, including: subjecting a portion of the mixture to a first spray drying device for first spray drying to obtain a first raw material, wherein the inlet temperature of the first spray drying device is 250-320°C, the outlet temperature is 100-120°C, and the air inlet volume is 4-6 m³ / h. 3 / h; The remaining mixture is subjected to a second spray drying in a second spray drying unit to obtain a second raw material, wherein the inlet temperature of the first spray drying unit is 250-320℃, the outlet temperature is 100-120℃, and the air inlet volume is 7-10m³ / h. 3 / h.
[0035] In a preferred embodiment, the temperature of the oxygen-free sintering process is 500–900°C, and the sintering time is 2–8 hours. The temperature and sintering time of the oxygen-free sintering process include, but are not limited to, the above ranges, which are beneficial for further improving the crystallinity of lithium titanate, thereby improving the reversibility of lithium-ion migration and ultimately enhancing its cycle performance.
[0036] Another aspect of this application provides a lithium titanate composite material, which is prepared using the preparation method provided in this application, or the composition of the lithium titanate composite material is based on Li4Ti5O. 12 / C style representation.
[0037] After sequentially mixing and granulating the aforementioned titanium-lithium composite with a first conductive agent, the first conductive agent can be physically coated onto the surfaces of the titanium and lithium sources, yielding first and second raw materials with different particle sizes. By performing oxygen-free sintering under an inert atmosphere, carbon-coated lithium titanate composite materials (first sintered product and second sintered product) with different particle sizes can be obtained. Because the two sintered products have different particle sizes, when applied to metal current collectors to form battery electrodes, the smaller-particle-size second sintered raw material can fill the voids in the first sintered product. This increases the compaction density, and the presence of the carbon coating layer also contributes to high compaction density and rate performance. In summary, the lithium titanate composite material prepared using the above method has high compaction density, and the resulting battery exhibits high energy density and rate performance.
[0038] Another aspect of this application provides a battery electrode, including a metal current collector and a conductive coating coated on the surface of the metal current collector. The material forming the conductive coating includes a lithium titanate composite material, a second conductive agent, and a binder, wherein the lithium titanate composite material is a lithium titanate composite material prepared using the preparation method provided in this application.
[0039] The lithium titanate composite material prepared by the above method has a high compaction density, and therefore the battery electrode prepared by mixing it with the second conductive agent and the binder also has high rate performance and energy density.
[0040] The second conductive agent can be selected from those commonly used in the field, including but not limited to one or more of the group consisting of carbon nanotubes, carbon fibers, graphene, carbon black and superconducting carbon black.
[0041] In a preferred embodiment, the weight ratio of the first sintered product to the second sintered product in the lithium titanate composite material is 1:9 to 9:1. The weight ratio of the first sintered product to the second sintered product includes, but is not limited to, the above range. Limiting it to this range is beneficial for further increasing the compaction density of the lithium titanate composite material, thereby improving the battery melting and energy density of the battery electrode formed therefrom. More preferably, the weight ratio of the lithium titanate composite material, the second conductive agent, and the binder is (90-96):(5-2):(5-2).
[0042] A fourth aspect of this application also provides a lithium-ion battery, including a battery electrode, which is the battery electrode provided in this application.
[0043] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.
[0044] Example 1
[0045] A method for preparing a lithium titanate composite material includes:
[0046] 1) Wet grinding: Titanium source and lithium source are wet-mixed and ground. The titanium source is 500g of titanium dioxide and the lithium source is 162g of lithium carbonate. The solid content of the grinding is 15%, the effective power is 1kW, the grinding power consumption is 5kwh / kg, and the particle size after grinding is D. 50 It is 0.06μm.
[0047] 2) Mixing: After grinding, add 1% carbon nanotubes as the first conductive agent based on the total weight of titanium and lithium sources, reduce the ball mill speed, and mix at low speed for 3 hours.
[0048] 3) Spray drying: The ground slurry is spray-dried at an inlet temperature of 250℃ and an outlet temperature of 105℃. The air inlet volume is set at 5.4 m³ / s. 3 The spray drying process produces powder material A with a particle size D50 of 11.5 μm at a rate of 9.6 m³ / h. 3 / h, spray drying produces powder material B with a particle size D50 of 4.8μm.
[0049] 4) Sintering: The spray-dried materials A and B are sintered at a temperature of 760℃. The sintered materials are C and D.
[0050] 5) Mixing: The materials C and D with different particle size distributions after sintering are mixed in different proportions, and the mixed material is E.
[0051] 6) Drying: The mixed lithium titanate powder is dried in a vacuum oven at a temperature of 105℃.
[0052] 7) Morphology testing: SEM analysis of the lithium titanate composite powder showed that its morphology was spherical, as shown in the image. Figure 1 and 2 As shown.
[0053] 8) Slurry preparation: Mix lithium titanate composite material, second conductive agent (superconducting carbon black), and binder (Arkema 900) in a mass ratio of 90:5:5 until uniform, and coat the mixture with an automatic heating coating machine to form electrode sheets.
[0054] 9) Drying the electrode sheets: The prepared electrode sheets are dried by forced air drying and vacuum drying.
[0055] 10) The compacted density of the electrode sheet after testing and rolling was 2.35 g / cm³. 3 SEM images of electrode surface and cross-section, such as Figures 3 to 5 As shown; the tested capacity is 168.6 mAh / g, as... Figure 6 As shown in the figure. Its rate capability is shown in Table 1.
[0056] Example 2
[0057] The difference from Example 1 is that 5% of a first conductive agent is added based on the total weight of the titanium source and the lithium source.
[0058] The compacted density of the electrode sheet after testing and rolling was 2.40 g / cm³. 3 The tested capacity was 168.8 mAh / g.
[0059] Example 3
[0060] The difference from Example 1 is that 8% of a first conductive agent is added based on the total weight of the titanium source and the lithium source.
[0061] The compacted density of the electrode sheet after testing and rolling was 2.21 g / cm³. 3 The tested capacity was 165.9 mAh / g.
[0062] Example 4
[0063] The difference from Example 1 is that the weight ratio of titanium source to lithium source is 1:1.3.
[0064] The compacted density of the electrode sheet after testing and rolling was 2.33 g / cm³. 3 The tested capacity was 160.1 mAh / g.
[0065] Example 5
[0066] The difference from Example 1 is that the particle size of the titanium source and lithium source is 0.3 μm after wet grinding.
[0067] The compacted density of the electrode sheet after testing and rolling was 2.20 g / cm³. 3 The tested capacity was 165.4 mAh / g.
[0068] Example 6
[0069] The difference from Example 1 is that the particle size of the titanium source and lithium source is 1 μm after wet grinding.
[0070] The compacted density of the electrode sheet after testing and rolling was 2.15 g / cm³. 3 The tested capacity was 161.5 mAh / g.
[0071] Example 7
[0072] The difference from Example 1 is that the oxygen-free sintering temperature is 650°C.
[0073] The compacted density of the electrode sheet after testing and rolling was 2.13 g / cm³. 3 The tested capacity was 155.0 mAh / g.
[0074] Example 8
[0075] The difference from Example 1 is that the oxygen-free sintering temperature is 1000℃.
[0076] The compacted density of the electrode sheet after testing and rolling was 2.19 g / cm³. 3 The tested capacity was 151.6 mAh / g.
[0077] Comparative Example 1
[0078] A method for preparing a lithium titanate composite material includes:
[0079] 1) Wet grinding: Titanium source and lithium source are wet-mixed and ground. The titanium source is 500g of titanium dioxide and the lithium source is 162g of lithium carbonate. The solid content of the grinding is 15%, the effective power is 1kW, the grinding power consumption is 5kwh / kg, and the particle size after grinding is D. 50 It is 0.06μm.
[0080] 2) Spray drying: The ground slurry is spray-dried at an inlet temperature of 250℃ and an outlet temperature of 105℃. The air inlet volume is set to 4.3m³. 3 The spray-drying process produces powder material A with a particle size D50 of 12.6 μm at a rate of 8.5 m³ / h. 3 / h, spray drying produces powder material B with a particle size D50 of 6.5μm.
[0081] 3) Sintering: The spray-dried materials A and B are sintered at a temperature of 760℃. The sintered materials are C and D.
[0082] 4) Mixing: The materials C and D with different particle size distributions after sintering are mixed in different proportions, and the mixed material is E.
[0083] 5) Drying: The mixed lithium titanate composite powder is dried in a vacuum oven at a temperature of 105℃.
[0084] 6) Slurry preparation: Mix the above lithium titanate composite material, the second conductive agent (superconducting carbon black), and the binder (Arkema 900) in a mass ratio of 90:5:5 evenly, and coat them with an automatic heating coating machine to make electrode sheets.
[0085] 7) Electrode drying: The prepared electrode is dried by forced air drying and vacuum drying.
[0086] 8) The prepared electrode sheets were rolled using an electric roller mill. The compacted density of the electrode sheets after rolling was tested to be 2.28 g / cm³. 3 The prepared electrode was made into a button cell (refer to GB / T30836-2014 Lithium titanate and its carbon composite anode material for lithium-ion batteries). The specific capacity was tested to be 167.4 mAh / g, and its rate performance is shown in Table 1.
[0087] Comparative Example 2
[0088] The difference from Example 1 is that the particle size D50 of the first raw material is 20 μm, and the particle size D50 of the second raw material is 1 μm.
[0089] The compacted density of the electrode sheet after testing and rolling was 2.05 g / cm³. 3 The tested capacity was 159.8 mAh / g.
[0090] Comparative Example 3
[0091] The difference from Example 1 is that the sintering process is an aerobic sintering process, and the sintering is carried out in an air atmosphere.
[0092] The compacted density of the electrode sheet after testing and rolling was 2.19 g / cm³. 3 The tested capacity was 165.3 mAh / g.
[0093] Table 1
[0094]
[0095] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:
[0096] Comparing Examples 1 to 8 and Comparative Examples 1 to 3, it can be seen that the lithium titanate composite material prepared by the preparation method provided in this application has a higher compaction density and better rate performance.
[0097] Comparing Examples 1 to 4, it can be seen that limiting the amount of the first conductive agent and the molar ratio of lithium to titanium in the titanium source and lithium source to the preferred range of this application is beneficial to further improve the lithium titanate composite material to have a higher compaction density and better rate performance.
[0098] Comparing Examples 1, 5, and 6, it can be seen that limiting the particle size of the titanium source and lithium source to the preferred range of this application is beneficial to further improve the lithium titanate composite material to have a higher compaction density and better rate performance.
[0099] Comparing Examples 1, 7, and 8, it can be seen that limiting the temperature of oxygen-free sintering to the preferred range of this application is beneficial to further improve the lithium titanate composite material to have a higher compaction density and better rate performance.
[0100] It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in a sequence other than those described herein.
[0101] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a lithium titanate composite material, characterized in that, The preparation method of the lithium titanate composite material includes: Titanium source, lithium source and first conductive agent are mixed and granulated in sequence to obtain first raw material and second raw material. The particle size D50 of the first raw material is 9 to 15 μm and the particle size D50 of the second raw material is 3 to 7 μm. Under an inert atmosphere, the first raw material and the second raw material are subjected to oxygen-free sintering to obtain a first sintered product and a second sintered product. The lithium titanate composite material is a mixture of the first sintered product and the second sintered product. Before the mixing process, the preparation method of the lithium titanate composite material further includes wet grinding of the titanium source and the lithium source; the wet grinding process has a grinding solid content of 10-30%, an effective power of 0.99-1 kW, a grinding power of 2-10 kWh / kg, and a particle size D50 of 0.05-0.3 μm after grinding.
2. The method for preparing the lithium titanate composite material according to claim 1, characterized in that, The titanium source is selected from titanium dioxide and / or metatitanic acid, and the lithium source is selected from lithium hydroxide and / or lithium carbonate. The first conductive agent is selected from one or more of the group consisting of carbon nanotubes, carbon fibers, graphene, and carbon black; The molar ratio of lithium in the titanium source to titanium in the lithium source is 1:1.2 to 1:1.25; The weight of the first conductive agent accounts for 1 to 5 wt% of the total weight of the titanium source and the lithium source.
3. The method for preparing the lithium titanate composite material according to claim 1, characterized in that, The granulation process includes: A portion of the mixture is subjected to a first spray drying process in a first spray drying apparatus to obtain the first raw material. The first spray drying apparatus has an inlet temperature of 250–320°C, an outlet temperature of 100–120°C, and an air inlet volume of 4–6 m³ / s. 3 / h; The remaining mixture is subjected to a second spray drying process in a second spray drying apparatus to obtain the second raw material. The inlet temperature of the first spray drying apparatus is 250–320°C, the outlet temperature is 100–120°C, and the air intake rate is 7–10 m³ / s. 3 / h.
4. The method for preparing the lithium titanate composite material according to claim 1, characterized in that, The temperature of the oxygen-free sintering process is 650–900℃, and the sintering time is 2–8 hours.
5. A lithium titanate composite material, characterized in that, The lithium titanate composite material is prepared by the preparation method according to any one of claims 1 to 4, wherein the composition of the lithium titanate composite material is based on Li4Ti5O. 12 / C style representation.
6. A battery electrode, comprising a metal current collector and a conductive coating coated on the surface of the metal current collector, characterized in that, The materials forming the conductive coating include a lithium titanate composite material, a second conductive agent, and a binder, wherein the lithium titanate composite material is a lithium titanate composite material prepared by any one of the preparation methods described in claims 1 to 4.
7. The battery electrode according to claim 6, characterized in that, In the lithium titanate composite material, the weight ratio of the first sintered product to the second sintered product is 1:9 to 9:
1.
8. The battery electrode according to claim 7, characterized in that, The weight ratio of the lithium titanate composite material, the second conductive agent, and the binder is (90-96): (5-2): (5-2).
9. A lithium-ion battery, comprising battery electrodes, characterized in that, The battery electrode is the battery electrode as described in any one of claims 6 to 8.
Citation Information
Patent Citations
Preparation method of high-tap-density lithium titanate material
CN103840146A
Lithium ion battery material preparation method
CN106374085A
Artificial graphite, preparation method and application thereof
CN110127687A